Music: Its Theologies and Spiritualities A Global Perspective - Foley, Edward (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This volume is an exploration of the varied and sometimes unrecognized ways in which music-especially in ritual contexts-can serve as both a spiritual conduit as well as a theological source. With topics ranging from a Congolese choir in Ireland to the Orthodox chant in Georgia, from postmodern reflections on new Passion compositions to reflections on the sacramentality of Black gospel music, this volume offers a rich plumbing of very diverse yet well researched musical traditions-case studies from around the globe-for their spiritual and theological contributions.